2011
DOI: 10.1104/pp.111.182667
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Deficiency of the Arabidopsis Mutant pad2-1 Affects Oxidative Stress-Related Events, Defense Gene Expression, and the Hypersensitive Response      

Abstract: The Arabidopsis (Arabidopsis thaliana) phytoalexin-deficient mutant pad2-1 displays enhanced susceptibility to a broad range of pathogens and herbivorous insects that correlates with deficiencies in the production of camalexin, indole glucosinolates, and salicylic acid (SA). The pad2-1 mutation is localized in the GLUTAMATE-CYSTEINE LIGASE (GCL) gene encoding the first enzyme of glutathione biosynthesis. While pad2-1 glutathione deficiency is not caused by a decrease in GCL transcripts, analysis of GCL protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 88 publications
3
68
0
1
Order By: Relevance
“…Under the first hypothesis, the oxt6 mutation would be expected to prevent the 2-fold increase in ICS1 expression in the mips1 mutant caused by transfer to LD conditions, and this misregulation could account for cell death suppression. Indeed, impairment of ICS1 induction upon pathogen infection in the pad2-1 mutant has been proposed to account for the impaired SA signaling observed in this mutant (Dubreuil-Maurizi et al, 2011). Based on genome-wide analysis (Thomas et al, 2012) and our assays, ICS1 is unlikely to be a direct target of CPSF30.…”
Section: Cpsf30 Positively Regulates Sa-mediated Immunity In Arabidopsismentioning
confidence: 99%
“…Under the first hypothesis, the oxt6 mutation would be expected to prevent the 2-fold increase in ICS1 expression in the mips1 mutant caused by transfer to LD conditions, and this misregulation could account for cell death suppression. Indeed, impairment of ICS1 induction upon pathogen infection in the pad2-1 mutant has been proposed to account for the impaired SA signaling observed in this mutant (Dubreuil-Maurizi et al, 2011). Based on genome-wide analysis (Thomas et al, 2012) and our assays, ICS1 is unlikely to be a direct target of CPSF30.…”
Section: Cpsf30 Positively Regulates Sa-mediated Immunity In Arabidopsismentioning
confidence: 99%
“…However, we showed that pad2-1 contains only 48% of wild-type GCL amount. 16 Based on these results, one hypothesis suggests that pad2-1 mutation could affect GCL protein folding or degradation leading to glutathione deficiency and correlated with cysteine accumulation (Fig. 1.1).…”
Section: The Deficiency Of Glutathione Is Related To a Low Content Ofmentioning
confidence: 99%
“…16 Our hypothesis is that the less reducing E GSH could affect the corresponding gene expression and/or enzyme activity or upstream signaling events. From these results and based on previous studies, their impairment might explain the weak HR establishment observed in pad2-1 during P. brassicae interaction.…”
Section: Pad2-1 Senses a Permanent Oxidative Stressmentioning
confidence: 99%
See 2 more Smart Citations